IMGT/mAb-KG: the knowledge graph for therapeutic monoclonal antibodies - Sanou, Gaoussou; Manso, Taciana; Todorov, Konstantin; Giudicelli, Véronique; Duroux, Patrice; Kossida, Sofia (Frontiers in Immunology, 2024)
Therapeutic monoclonal antibodies have demonstrated promising outcomes in diverse clinical indications, including but not limited to graft rejection, cancer, and autoimmune diseases lately. Given the importance of having fast and easy access to reliable information about therapeutic monoclonal antibodies for the scientific community involved in monoclonal antibody development, IMGT®, the international ImMunoGeneTics information system®, is offering a unique and valuable resource, namely IMGT/mAb-DB, a database of monoclonal antibodies with therapeutic applications. To connect IMGT/mAb-DB with the rest of the IMGT databases, we created IMGT/mAb-KG, a knowledge graph for therapeutic monoclonal antibodies connected to IMGT structures and genomics databases. IMGT/mAb-KG is developed using the most effective methodologies and standards of semantic web and acquires data from IMGT/mAb-DB.Concerning the interoperability aims, IMGT/mAb-KG reuses terms from biomedical resources and is connected to related resources. In addition to freely providing access to 1489 monoclonal antibodies, IMGT/mAb-KG also provides access to the knowledge associated with them, including their mechanism of action, their construction, and their link to external resources. Furthermore, we provide a user-friendly web interface that allows exploration and analysis of IMGT/mAb-KG content.